ANALISIS VARIANS BIAYA PRODUKSI AIR BERSIH PADA PDAM TIRTA KENCANA SAMARINDA TAHUN 2017-2018 - Retno Maninggar Jati; Khairil Akbar; Diah Lika Ningtyas (Politeknik Negeri Samarinda, 2019)
This study aims to determine the amount of the difference between the budget for production costs and realization and to find out the causes of the difference in production costs in 2017-2018. The method used in this study is the variance in raw material costs, labor costs, and factory overhead costs. The results of the analysis in 2017-2018 are known to occur in the total beneficial difference in the cost of raw materials with the value of each year amounting to Rp 11,471,520,000.00 and Rp15,786,734,500.00. The total difference in direct labor costs has a beneficial difference in 2017-2018 of Rp 2,286,118,743.81 and Rp 1,624,088,292.00. Whereas for the total difference in factory overhead costs in 2017-2018, there was a favorable difference with the value of each year amounting to Rp 3,602,637,118.19, and Rp4,284,051,954.26. Keywords: Budget, Variance, Production.